MEDIA PERMAINAN ULAR TANGGA MODIFIKASI TERHADAP KEMAMPUAN BERHITUNG PENJUMLAHAN ANAK TUNANETRA PADA SEKOLAH LUAR BIASA - Sindi Nur Ismawati, Elisa (Jurnal Pendidikan Khusus, 2017)
Abstract: This research was based on the problems experienced by stduents with visual impairment who has not been able to count the sum. The learning process used in improving the ability to count the sum was by using the modified snake and ladders game media. Through modified snake and ladders game media visual impairment students was actively stimulated to do learning activities while playing. This research aims to prove the influence of modified snake and ladders game media to the ability to count the sum of visual impairment students in special school. This research used quantitative approach, with research type of pre-experimental study, and research design one-group pretest-posttest design. The samples in this study are all students with visual impairment in grade IV A SLB-A YPAB Tegalsari Surabaya which amounted to 6 students with ability to count the sum were still need to be developed. Technique of collecting data by using observation and test. Data were analyzed using non-parametric statistics by Wilcoxon Match Pairs Test. Research results indicate that there is an increase in the count the sum ability at the time of the initial observation (pre-test) obtain an average value of 50 and at the end of the observation (post-test) obtain an average value of 88.33. In addition, the results also showed that = 2, 20 is greater than the value, it can be seen that gained 2.20 value greater than 5% error level (two-sided test) is 1.96 () so rejected and accepted. Based on these results it is evident that there is an influence in the use of modified snake and ladders game media on the ability to count the number of visual impairment students in special school. Keywords: modified snake and ladders game media, count the sum